Randomized Controlled Clinical Trial Comparing Transurethral Eneucleation and Resection of Prostate and Trans-urethral Resection of Prostate in the Management of Benign Prostatic Hyperplasia (BIRDEM Medical Journal, 2017)
Background: Transurethral resection of prostate (TURP) is the predominant surgical procedure for benign prostatic hypertension (BPH) but is not devoid of complications like capsular perforation, drop in Hb%, drop in Na+, residual adenoma; hence endeavors are evolving to combat such complications. A newer technique transurethral enucleation and resection of prostate (TUERP) has been devised to solve these problems. This study was designed to compare the safety and the efficacy of newer technique, TUERP with widely practiced TURP Methods: This randomized controlled trial was done at BSMMU, after getting ethical approval from the ethical review committee of the institute, from January to October, 2009. A total of 60 BPH patients were purposively enrolled in this study, after obtaining informed written consent and they were randomized as control, Group A (30 patients, underwent TURP) and experimental group, Group B (30 patients, underwent TEURP).Results: The mean preoperative Hb% level of Group A was 15.1 gm% (SD ± 0.5) and perioperative Hb% level was 13.04 gm% (SD ± 6.06). There was significant difference (P 0.05). The mean preoperative Na + of Group A was 140 mmol/l (SD ± 4.1) and perioperative Na+ was 126 mmol/l (SD ± 6.8). There was significant difference (P0.05).Conclusion: TUERP eliminates drop in Hb% and Na+which are usual consequences following TURP. Thus TUERP can be advocated in the treatment of BPH as it also allows completeresection down to surgical capsule.Birdem Med J 2017; 7(3): 216-220